Discrepancies in Estimates of Prevalence and Correlates of Substance Use and Disorders Between Two National Surveys - Grucza, Richard A. (2007)
AIM: To assess the degree to which methodological differences might influence estimates of prevalence and correlates of substance use and disorders by comparing results from two recent surveys administered to nationally representative U.S. samples. METHODS: Post-hoc comparison of data from the 2002 National Survey on Drug Use and Health (NSDUH) to data from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) administered in 2001-02. RESULTS: Prevalence estimates for all substance use outcomes were higher in the NSDUH than in the NESARC; ratios of NSDUH to NESARC prevalences ranged from 2.1 to 5.7 for illegal drug use outcomes. In the NSDUH, past-year substance use disorder (SUD) prevalence estimates were higher for cocaine and heroin, but were similar to NESARC estimates for alcohol, marijuana, and hallucinogens. However, prevalence estimates for past-year SUD conditional on past-year use were substantially lower in the NSDUH for marijuana, hallucinogens, and cocaine. Associations among drug and SUD outcomes were substantially higher in the NESARC. Total SUD prevalence did not differ between surveys, but estimates for Blacks and Hispanics were higher in the NSDUH. CONCLUSION: There are a number of methodological variables that might have contributed to such discrepancies; among plausible candidates are factors related to privacy and anonymity, which may have resulted in higher use estimates in the NSDUH, and differences in SUD diagnostic instrumentation, which may have resulted in higher SUD prevalence among past-year substance users in the NESARC.